Ответы и объяснения

2014-02-03T13:15:57+00:00
Xy+3y-2x-6+2x-3y+1=xy-5
x=4 \sqrt{2} ; y= \sqrt{2}
xy-5=4 \sqrt{2} * \sqrt{2} -5=4*2+5=13

 \frac{24a^5y^4}{(2a^2y)^3} = \frac{24a^5y^4}{8a^6y^3}=\frac{3y}{a}

4px+3py-4qx-3qy=4px-4qx-3qy+3py=4x(p-q)-3y(q-p)=4x(p-q)+3y(p-q)=
(p-q)(4x+3y)

 \frac{9a^2+b^2+6ab}{3} * \frac{6}{3a+b} = \frac{(3a+b)^2}{3} * \frac{6}{3a+b}= 6a+3b
2014-02-03T13:26:51+00:00
1) = xy-2x+3y+2x-3y+1=xy+1
4корней из 2 * корень из 2 + 1= 4*2+1=9
2)24a^5*y^4/(8a^6*y^3)=3y/a
3)=(4px-4qx)+(3py-3qy)=(4x+3y)(p-q)
4)=((3a+b)^2 * 6)/3(3a+b)=6a+2b